Asian Development Bank–Japan scholarship program annual report 2022 (Annual Reports of the Asian Development Bank-Japan Scholarship Program)
This publication details the activities, achievements, and success stories of Asian Development Bank (ADB)–Japan Scholarship Program (JSP) alumni in 2022.